A recepção de nietzsche no brasil: renovação e conservadorismo - Dias, Geraldo Pereira [UNIFESP] (2019)
This thesis aims to investigate the way in which the reception of Nietzsche's philosophy occurred between 1876 and 1945 in Brazil. In order to do so, I argue that given the characteristics of the first reception of Nietzsche's philosophy, between Germanist and pre-modernist authors, two contrasting aspects of the Brazilian modernist literary movement were accentuated: on the one hand, critical-literary and essay-interpretive renewal, and, on the other hand, political-ideological conservatism. As a means of proving this hypothesis, I examine, at the beginning, how the first material about Nietzsche arrived in the country, particularly among the authors of the Germanist movement, who, from 1876, made the first readings and translations of Nietzschean philosophy from the German language. Next, I investigate the way in which the reception of Nietzsche's philosophy in premodernism occurs, which, unlike the Germanist movement, was branded as French loans, as in the works of authors like José Veríssimo, Albertina Bertha and Elísio de Carvalho. Finally, I analyzed the reception of Nietzsche's philosophy in the modernist movement, with emphasis on the essays-interpretative and critical-literary writings of Paulo Prado, Gilberto Freyre and Sérgio Buarque de Holanda, produced between 1922 and 1945.